Introducing a 3‐dimensionally Printed, Tissue‐Engineered Graft for Airway Reconstruction: A Pilot Study. (21st September 2015) - Goldstein, Todd A.; Smith, Benjamin D.; Zeltsman, David; Grande, Daniel; Smith, Lee P.
Abstract : Objective: To use 3‐dimensional (3D) printing and tissue engineering to create a graft for laryngotracheal reconstruction (LTR). Study Design: In vitro and in vivo pilot animal study. Setting: Large tertiary care academic medical center. Subjects and Methods: A 3D computer model of an anterior LTR graft was designed. That design was printed with polylactic acid on a commercially available 3D printer. The scaffolds were seeded with mature chondrocytes and collagen gel and cultured in vitro for up to 3 weeks. Scaffolds were evaluated in vitro for cell viability and proliferation. Anterior graft LTR was performed on 9 New Zealand white rabbits with the newly created scaffolds. Three animals were sacrificed at each time point (4, 8, and 12 weeks). The in vivo graft sites were assessed via bronchoscopy and histology. Results: The in vitro cell proliferation assay demonstrated initial viability of 87.5%. The cells proliferated during the study period, doubling over the first 7 days. Histology revealed that the cells retained their cartilaginous properties during the 21‐day study period. In vivo testing showed that all animals survived for the duration of the study. Bronchoscopy revealed a well‐mucosalized tracheal lumen with no evidence of scarring or granulation tissue. Histology indicated the presence of newly formed cartilage in the region where the graft was present. Conclusions: Our results indicate that it is possible to produce a custom‐designed, 3D‐printed, tissue‐engineered graft for airway reconstruction.